Clustering of energy balance-related behaviors among youth: overview and implications - Mello, Gabrielli Thais de (2024)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Desportos, Programa de Pós-Graduação em Educação Física, Florianópolis, 2024.